A fluorescence-based assay suitable for quantitative analysis of deadenylase enzyme activity - Maryati, Marayti; Kaur, Ishwinder; Jadhav, Gopal P.; Olotu-Umoren, Loyin; Oveh, Blessing; Hashmi, Lubna; Fischer, Peter M.; Winkler, G. Sebastiaan (Oxford Journals, 2013)
In eukaryotic cells, the shortening and removal of the poly(A) tail of cytoplasmic mRNA by deadenylase enzymes is a critical step in posttranscriptional gene regulation. The ribonuclease activity of deadenylase enzymes is attributed to either a DEDD (Asp-Glu-Asp-Asp) or an endonuclease–exonuclease–phosphatase domain. Both domains require the presence of two Mg2+ ions in the active site. To facilitate the biochemical analysis of deadenylase enzymes, we have developed a fluorescence-based deadenylase assay. The assay is based on end-point measurement, suitable for quantitative analysis and can be adapted for 96- and 384-well microplate formats. We demonstrate the utility of the assay by screening a chemical compound library, resulting in the identification of non-nucleoside inhibitors of the Caf1/CNOT7 enzyme, a catalytic subunit of the Ccr4–Not deadenylase complex. These compounds may be useful tools for the biochemical analysis of the Caf1/CNOT7 deadenylase subunit of the Ccr4–Not complex and indicate the feasibility of developing selective inhibitors of deadenylase enzymes using the fluorescencebased assay.